The Oxford handbook of wisdom and the Bible - Kynes, Will 1981- (Oxford Oxford University Press, Incorporated, 2021)
A high-profile and authoritative volume in which a broad range of leading scholars in the field assess the current "state of the art" in the study of both Wisdom Literature as a category of texts in the Hebrew Bible and as a concept more generally. This particularly timely handbook captures the field at a time in which a plethora of new questions are being asked about Wisdom Literature and spans the gap between that cutting-edge scholarship and standard textbook expositions.
Cover -- Wisdom and The Bible -- Copyright -- Dedication -- Contents -- List of Abbreviations -- List of Contributors -- Chapter 1: Wisdom and Wisdom Literature: Past, Present, and Future -- 1.1 Wisdom as Concept and Category -- 1.2 Past -- 1.3 Present -- 1.3.1 The Traditional View -- 1.3.2 Pan-Sapientialism -- 1.3.3 Sapiential Minimalism -- 1.4 Future -- 1.5 Conclusion -- Works Cited -- Part I: The Concept Of Wisdom In The Hebrew Bible -- Chapter 2: Advice: Wisdom, Skill, and Success -- 2.1 Wisdom and Canon -- 2.2 Vocabulary -- 2.3 Case Study: Vocabulary of Proverbs 1:2-7 -- 2.4 Literary Form -- 2.5 Advice -- 2.6 Transmission through Instruction -- Works Cited -- Chapter 3: Epistemology: Wisdom, Knowledge, and Revelation -- 3.1 Experience and Reasoning -- 3.2 Tradition -- 3.3 Skepticism -- 3.4 Revelation -- 3.5 Conclusions -- Works Cited -- Chapter 4: Virtue and its Limits in the Wisdom Corpus: Character Formation, Disruption, and Transformation -- 4.1 Wisdom and Virtue -- 4.2 Proverbs: Ethics of Formation -- 4.2.1 Efficacy of Virtue -- 4.2.2 "Happiness" in Proverbs -- 4.2.3 Narrativity of the Self -- 4.3 Job: Ethics of Encounter -- 4.3.1 Virtue's Efficacy? -- 4.3.2 Eulogy over Eudaimonia -- 4.3.3 Ethics of Encounter -- 4.3.4 Narrativity of the Self: Job's Integrity -- 4.3.5 Eudaimonia Regained? -- 4.4 Ecclesiastes: "Ethics" of Enjoyment -- 4.4.1 Moral Lack -- 4.4.2 "Ethics" of Enjoyment -- 4.5 Conclusion -- Works Cited -- Chapter 5: Theology: Creation, Wisdom, and Covenant -- 5.1 Creation: Cosmos and History -- 5.2 Wisdom as a Concept -- 5.3 Presuppositions and Conditions for Wisdom -- 5.3.1 Fear of the Lord -- 5.3.2 Knowledge and Praxis According to the General Patterns of Reality -- 5.3.3 Knowledge and Right Action in Relation to Individual Realities -- 5.3.4 Tradition -- 5.3.5 Excellence -- 5.4 What Does Wisdom Do?.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books